2015
DOI: 10.1590/0102-311x00086814
|View full text |Cite
|
Sign up to set email alerts
|

Social conditions and urban environment associated with participation in the Ciclovia program among adults from Cali, Colombia

Abstract: The Ciclovia program (CP) has emerged as an effective initiative to promote active living in urban spaces in Latin America. This study assessed the association between social conditions, the urban environment and participation in the CP among adults living in the city of Cali, Colombia. A cross-sectional study was conducted in 2011 and 2012 among 719 adults aged 18 to 44. Urban environment measures were obtained using Geographic Information Systems. A multilevel logistic regression was used for the analysis. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…Participants from other Ciclovia programs spent between 56 to 180 min in a 3 to 7 h event [21,22,23,24,25,27,28,29,30,31,32]. The cities of Latin American countries have some of the longest programs ranging from 20.5 to 75 miles [9,30,32]. We found that 88.4% of the MEB users accumulated enough MVPA during the event to meet the weekly physical activity recommendations proposed by the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…Participants from other Ciclovia programs spent between 56 to 180 min in a 3 to 7 h event [21,22,23,24,25,27,28,29,30,31,32]. The cities of Latin American countries have some of the longest programs ranging from 20.5 to 75 miles [9,30,32]. We found that 88.4% of the MEB users accumulated enough MVPA during the event to meet the weekly physical activity recommendations proposed by the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…For example, surveys conducted with Colombian adults in Bogota showed that people who participated in the community-based “Ciclovia Program” were significantly more likely to cycle for transportation [ 37 ]. Another study conducted in Cali, Colombia, showed that adults’ participation in the “Ciclovia Program” was associated positively with the presence of a “Ciclovia corridor”, which are streets closed for cars and open for walking or cycling on weekends and public holidays [ 38 ]. The longitudinal study “Cycling Connecting Communities” conducted with adults in Sydney, Australia, based on a social marketing framework and behavior change theories, found that after two years people who received the intervention had a significant likelihood of using bike paths [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal study “Cycling Connecting Communities” conducted with adults in Sydney, Australia, based on a social marketing framework and behavior change theories, found that after two years people who received the intervention had a significant likelihood of using bike paths [ 28 ]. In addition, other variables are associated with cycling for transportation such as self-efficacy, physical activity habit, attitude, and social support [ 29 , 38 ]. Finally, we need better facilities in subways and train stations, such as permission to travel with bicycles, bicycle parking, and bicycle-share programs across the cities.…”
Section: Discussionmentioning
confidence: 99%
“…Various Latin American countries have set strategies, which have not yet been evaluated, to increase awareness about the harmful effects of transfatty acids ( 414 ) and of high salt intake ( 415 – 419 ). Other population-level initiatives include the creation of guidelines for healthful eating and PA; the creation of Ciclovía-Recreovía in Colombia ( 420 ), additional training of health care professionals to improve diabetes care, and diabetes screening initiatives in Chile, Argentina, and Honduras, nutrition labeling in Ecuador, and the ban of unhealthful foods in schools in Costa Rica, Perú and Guatemala ( 418 ). These new strategies present a unique opportunity to evaluate the process of implementation, the role of stakeholders in their design and implementation, and their eventual impact on anthropometric, lipids, and metabolic indicators or diabetes prevalence and treatment.…”
Section: Interventions To Prevent Type 2 Dm Among Hispanics/latinosmentioning
confidence: 99%